Supervision of the Grand Jury: Who Watches the Guardian? - Anne Bowen Poulin (Washington University Law Quarterly, 1990)
The first part of this Article reviews prior Supreme Court decisions and analyzes the three recent decisions to determine the precise extent to which they limit judicial supervision of the grand jury. The second part of the Article assesses the utility of the available mechanisms for enforcing procedural protections in the grand jury. This Article identifies the remedies available as enforcement mechanisms in the grand jury and considers the effectiveness of those remedies. The Article then examines whether the grand jury's shield function is still viable.
Keywords: Grand jury